2015
DOI: 10.1021/bm501649y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Photoluminescent F8BT Conjugated Polymer Nanoparticles Determines Protein Corona Formation and Internalization by Phagocytic Cells

Abstract: Conjugated polymer nanoparticles are being developed for a variety of diagnostic and theranostic applications. The conjugated polymer, F8BT, a polyfluorene derivative, was used as a model system to examine the biological behavior of conjugated polymer nanoparticle formulations stabilized with ionic (sodium dodecyl sulfate; F8BT-SDS; ∼207 nm; -31 mV) and nonionic (pegylated 12-hydroxystearate; F8BT-PEG; ∼175 nm; -5 mV) surfactants, and compared with polystyrene nanoparticles of a similar size (PS200; ∼217 nm; -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 52 publications
6
57
0
Order By: Relevance
“…While CN-PPV self-assembles and formed CPNs in the absence of amphiphilic stabilising molecules (100% CN-PPV formulation), the highly hydrophobic F8BT forms nanoparticles only in the presence of surfactants, and very low batch yields were obtained previously (<30%) 26 . The incorporation of conjugated polymers within a matrix of the amphiphilic PEG-PLGA diblock copolymers was found to be a successful strategy to improve product yields of these systems.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…While CN-PPV self-assembles and formed CPNs in the absence of amphiphilic stabilising molecules (100% CN-PPV formulation), the highly hydrophobic F8BT forms nanoparticles only in the presence of surfactants, and very low batch yields were obtained previously (<30%) 26 . The incorporation of conjugated polymers within a matrix of the amphiphilic PEG-PLGA diblock copolymers was found to be a successful strategy to improve product yields of these systems.…”
Section: Resultsmentioning
confidence: 90%
“…The red or near-infrared luminescence emission 16 of CN-PPV-based materials led to their use in cell labelling [17][18][19] , protein The material composition of CPNs influences their properties in biological fluids and cell culture media. For example, our earlier work has demonstrated that the type of surfactants used for nanoparticle assembly plays an important role in determining cellular uptake, biocompatibility and protein corona formation 26 (protein adsorption to nanoparticle surface after exposure to biological fluids 27 ). Surfactants containing poly(ethylene glycol) (PEG) are commonly used for steric stabilization since they form a hydrophilic layer on the surface of the nanoparticles that prevents interactions with blood components 28 .…”
Section: Introductionmentioning
confidence: 99%
“…With the inherent conjugated backbone, the latter have stipulated large interest outside the field of flexible electronics due to their excellent optical properties -fluorescence brightness, ideal photostability, fast radiative rate and nonblinking behavior -together with biocompatibility for use in the bioimaging field. [15][16][17] Among the different polymers poly(p-phenylene vinylene) (PPV), a pioneer material for the first organic light emitting diode (oLED) and since then one of the most thoroughly studied conjugated polymers, is of great interest owing to its reliable synthesis routes in combination with design flexibility offered by the recent control methodologies for realizing tailor-made functional PPVs, simple scale up potential and their well-known photophysical properties. [18][19][20] Though PPV derivatives are highly interesting as a fluorophore, their interaction with biological environments and performance as bioimaging probe have not yet been fully explored to date, the research emphasis laying predominantly on synthesis routes and inherent material characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26] They are indispensable for attaching biomolecules to impart for instance target specificity or a stealth 5 effect. Instead of being forced to use complex and tedious post-synthesis methods in a later stadium or surface adsorbed surfactant molecules 15 , functionalized PPVs synthesized via the sulfinyl precursor route offer an elegant alternative to introduce surface functional groups. By employing such custom-made PPV-derivatives for the NP formulation, the synthetic identity of the NP based bioimaging probe can be fine-tuned to meet the set out conditions in the biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…We have also studied the effect of surface chemistry of CPNs and how this affects uptake and internalisation in phagocytic cells 30 . We report the possibility of using silica to encapsulate a CP/pluronic micelle which is prepared using a modified bioinspired silification approach 31,32 .…”
Section: Introductionmentioning
confidence: 99%